The Influence of Organizational Climate on Employee Performance with Job Satisfaction as a Mediating Variable - Julindrastuti, Dijah; Karyadi, Iman (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
The fulfillment of basic needs is essential for individuals to ensure the well-being of themselves and their families. As members of the workforce, individuals possess skills that serve as a form of capital enabling them to work and fulfill these needs. Both the fulfillment of needs and the development of skills can be facilitated through organizations. In carrying out its activities, an organization requires employee support, as employees are a critical factor in determining its success. An organization that is able to create a positive work climate and provide job satisfaction in all aspects can influence employee performance in a positive direction. This, in turn, is expected to help the organization grow and achieve its goals. Good employee performance has a direct positive impact on organizational success. Creating comfort in the workplace can be achieved in various ways, such as addressing employee needs, appreciating employees, and fostering good cooperation. In addition to comfort—also referred to as a positive organizational climate—job satisfaction plays a key role in motivating employees to work optimally. Job satisfaction can be achieved through adequate salary, recognition, and fair treatment. Based on this rationale, the researcher conducted a study entitled “The Influence of Organizational Climate on Employee Performance with Job Satisfaction as a Mediating Variable.” The population of this study consisted of non-academic employees at a private higher education institution “X.” The sample included 50 non-academic employees with a minimum tenure of 20 years, selected using purposive sampling. To test the hypotheses, Structural Equation Modeling (SEM) was applied using AMOS 16.0 to examine the mediating role of job satisfaction. The findings reveal that organizational climate has a significant effect on employee performance (p = 0.000). However, organizational climate does not significantly affect job satisfaction (p = 0.154). Job satisfaction significantly influences employee performance (p = 0.000), but job satisfaction does not mediate the relationship between organizational climate and employee performance (p = 0.214).